The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.organomet.0c00525
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Cobalt Complexes Based on the trans Effect of Hybrid Ligands and Evaluation of their Catalytic Activity in the Cycloaddition of Carbon Dioxide with Epoxide

Abstract: A series of cobalt complexes are presented as effective catalysts for the synthesis of cyclic carbonates from epoxides and CO2. The catalytic potentials of the cobalt complexes, in combination with tetrabutylammonium bromide, have been demonstrated to solve some challenges in the synthesis of cyclic carbonates, including the room-temperature conversion of terminal epoxides and activation-challenging substrates such as internal epoxides and fatty acid derived epoxides. A key factor in the success of the strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
0
11
1
Order By: Relevance
“…It was found that the coupling reaction hardly proceeded with the complex 3 or TBAB as the sole catalyst (entries 10 and 11, Table ), with only 4.3% and 5.5% PO conversion into PC observed at 130 °C for 1.0 h, which is much lower than the yield of 69.8% for the 3 /TBAB binary system. This confirms that the presence of both a Lewis acidic bimetallic zinc complex and a Lewis base as a nucleophile is necessary for an ideal catalyst system to achieve high efficiency. , Furthermore, the outcome of this coupling reaction dramatically depended on the nature of the nucleophile employed as shown in entries 3 and 6–9 in Table . The binary system zinc complex 3 /TBAB afforded the best result.…”
Section: Results and Disscussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…It was found that the coupling reaction hardly proceeded with the complex 3 or TBAB as the sole catalyst (entries 10 and 11, Table ), with only 4.3% and 5.5% PO conversion into PC observed at 130 °C for 1.0 h, which is much lower than the yield of 69.8% for the 3 /TBAB binary system. This confirms that the presence of both a Lewis acidic bimetallic zinc complex and a Lewis base as a nucleophile is necessary for an ideal catalyst system to achieve high efficiency. , Furthermore, the outcome of this coupling reaction dramatically depended on the nature of the nucleophile employed as shown in entries 3 and 6–9 in Table . The binary system zinc complex 3 /TBAB afforded the best result.…”
Section: Results and Disscussioncontrasting
confidence: 69%
“…This confirms that the presence of both a Lewis acidic bimetallic zinc complex and a Lewis base as a nucleophile is necessary for an ideal catalyst system to achieve high efficiency. 40,41 Furthermore, the outcome of this coupling reaction dramatically depended on the nature of the nucleophile employed as shown in entries 3 and 6−9 in Table 1. The binary system zinc complex 3/TBAB afforded the best result.…”
Section: ■ Results and Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are consistent with the experiments of UV–vis spectra, suggesting that the interaction between the catalyst 1d and the epichlorohydrin was occurred. Our recent published work 28 reported the trans effect of cobalt complexes. In the report, we observed a characteristic absorption peak of IR for the acetylacetone in situ FT‐IR experiments for cobalt complexes, which supported the acetylacetone preferring to dissociate from the cobalt center.…”
Section: Resultsmentioning
confidence: 99%